“Diagnóstico de la existencia y uso de las maquinarias y aperos agrícolas en el Cantón Urdaneta, Provincia de Los Ríos en el año 2024” - Bea Quiñónez, Julio Alejandro (2024)
For this research, it is a survey type because a series of questions developed for a percentage of short cycle producers were asked on the topic of the existence and use of agricultural machinery and its implements in the Urdaneta Canton, Los Ríos Provinces. This research was carried out in order to know the use of agricultural machinery for both large, medium and small farmers. Our main objective is to evaluate the existence and use of agricultural machinery and implements in the canton and then detail the aspects of the machinery and what type of agricultural machinery that farmers use to work their land. Using the proportion methods formula, it was carried out to calculate the number of farmers who were interviewed in the field. As results, we obtained that most of the farmers surveyed are male, many have only finished primary school, their land is their own and few have more than 5 hectares, few belong to a farmers' association, the machinery with which they work their land is rented, so the majority are not satisfied with the cost of rent. Farmers plant rice mostly in the geographical area where the canton is located, but they still plant corn and very little soybeans, for the Planting these crops and cultural management of them use some machinery and its implements, the state in which they are found is used but they are still used for work.